DANAMICS OF LAND OWNERSHIP AND MANAGEMENT IN SMALL-SCALE IRRIGATION SCHEMES IN THE BAWKU EAST DISTRICT OF GHANA - Akudugu, Jonas Ayaribilla; Issahaku, Mustapha (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿﻿The construction and/or rehabilitation of smallholder irrigation schemes in the Upper East Region of Ghana has been seen as an important intervention in attempts to improve the livelihood schemes of the people in the region. However, the management of these smallholder irrigation schemes, particularly the administration of the irrigable lands has become problematic. Decentralized communal institutions like the Water Users Associations which were set up to ensure the effective management of these schemes have proven incapable of the task, particularly with regards to the management of the irrigable areas of these schemes. Not only has the Water Users Association lost control over the management of the irrigable lands, they have apparently become non-functional or non-existent in some of the communities. This has resulted in the emergence of multiple land owners who have now taken over the responsibility of the land allocation from the Water Users Association. This situation is not only denying people access to the irrigable land of smallholder community irrigation schemes; it is also creating tensions and potential conflicts that may be difficult to manage in the near future. This paper assesses land management in three smallholder irrigation schemes in the Bawku East District of the Upper East Region of Ghana. The paper concludes that unless the current arrangement regarding the ownership and management of smallholder irrigation schemes’ lands is revisited and/or re-organized, the role and relevance of these schemes as livelihood mechanisms will be undermined.